Failing to meet expectations: the meaning of Intimate Partner Violence for Pakistanis. (13th September 2011) - Ali, PA; O'Cathain, A; Naylor, PB; Croot, E
Abstract : Background: Intimate Partner Violence (IPV) is a major social and public health problem affecting people across cultures, religions and societies. Much research has been undertaken to offer understanding and explanations of this phenomenon, its determinants, and its consequences in developed countries around the world. However, there is still a paucity of research on IPV in many areas of the developing world such as Pakistan. Although various studies have been conducted to demonstrate the prevalence of IPV in the country, none of the studies have tried to explore the meaning of IPV from the perspective of Pakistani people. Aim: This study aimed to explore understandings of Pakistani men and women of IPV. It aimed to develop a theory to explain the meaning of IPV and the process through which it occurs, from the perspective of Pakistani people. Methods: The study utilised a qualitative approach with constructivist grounded theory methods and analysis techniques. Data was collected from Karachi, Pakistan and Sheffield, UK. Forty one people (20 from Pakistan and 21 from UK) participated in the study. Findings: The participants identified IPV as a serious concern. Although verbal abuse is often included in definitions of IPV, the participants did not consider shouting, raising the voice or scolding as a type of violence. Hitting, beating, pushing, throwing objects, and pulling hair were identified as acts of physical violence, and non-consensual sex was identified as a form of sexual abuse. Participants identified failure to meet role expectations of a husband or wife as a key contributor to the development of conflict between partners which could lead to IPV. Examples of various expectations from a wife include completing household chores, looking after husband, looking after children, looking after in laws, respecting and adjusting to in-law's customs and traditions. Important expectation from a husband include provision of finances, acting as a bridge, maintaining a balance between his wife and other family members particularly his mother and sisters, and taking the responsibility for his wife and children. Failure to meet these expectations could contribute to conflict and subsequent violence. This appeared to be shaped by cultural issues such as common use of arranged marriages, the rarity of divorce and the centrality of the extended family to the intimate partnership. Implications: Any interventions aimed at reducing IPV in Pakistani people must consider the meaning and causes of IPV from the perspective of that group.